Bio-Ethanol Production from Unrefined Sugar by Fermentation Using the Strain Saccharomyces cerevisiae - Jenish, S.; Venkatesan, S.; Kester Fernando, L. (Asian Journal of Chemistry, 2011)
In this study, Saccharomyces cerevisiae is used for bio-ethanol production from unrefined sugar under anaerobic condition. The parameters that influence the production of bio-ethanol from unrefined sugar are optimized. The optimal values of the parameters such as sugar concentration, enzyme concentration, temperature and pH are found to be 300 gm/L, 2 gm/L, 38 ºC and 4 respectively. Under this optimum operating conditions the maximum yield of bio-ethanol is 63 %. The rate of formation of bio-ethanol is found to be well fitted with Michaelis-Menten equation and the values of Vmax and Km are found to be 0.71 mol/L sec and 81.63 mol/L, respectively.